Personalized Medicine Is the Postgenomic Condition - Neuhaus, Carolyn P. (The Hastings Center report, 2018)
When President Obama laid out his vision for the U.S. Precision Medicine Initiative in a 2016 Boston Globe op-ed, he cautioned, “[I]t only works if we collect enough information first.” “Collecting information” is an apt way to describe the subject of both books reviewed here. Jenny Reardon's The Postgenomic Condition: Ethics, Justice, and Knowledge after the Genome traces the history of the Human Genome Project and efforts around the globe to obtain blood samples to extract not only genetic data but also meaning from them. Barbara Prainsack's Personalized Medicine: Empowered Patients in the 21st Century? concerns the capture of digital, quantifiable, and computable information about nearly all aspects of people's lives in the pursuit of personalized medicine. Reardon and Prainsack critique scientists’ and corporations’ appeals to liberal democracy, justice, and empowerment to collect more and more information about people. They reveal the limitations and frequent superficiality of those appeals and remind us that person-centric ethics rather than data-centric research is needed to realize a more democratic, just, and empowered society.